Transcatheter aortic valve‐in‐valve treatment of degenerative stentless supra‐annular Freedom Solo valves: A single centre experience. Issue 3 (17th June 2016) - Cockburn, James; Dooley, Maureen; Parker, Jessica; Hill, Andrew; Hutchinson, Nevil; de Belder, Adam; Trivedi, Uday; Hildick‐Smith, David
Abstract : Background: Redo surgery for degenerative bioprosthetic aortic valves is associated with significant morbidity and mortality. Report results of valve‐in‐valve therapy (ViV‐TAVI) in failed supra‐annular stentless Freedom Solo (FS) bioprostheses, which are the highest risk for coronary occlusion. Methods: Six patients with FS valves (mean age 78.5 years, 50% males). Five had valvular restenosis (peak gradient 87.2 mm Hg, valve area 0.63 cm 2 ), one had severe regurgitation (AR). Median time to failure was 7 years. Results: Patients were high risk (mean STS/Logistic EuroScore 10.6 15.8, respectively). FS valves ranged from 21 to 25 mm. Successful ViV‐TAVI was achieved in 4/6 patients (67%). Of the unsuccessful cases, (patient 1 and 2 of series) patient 1 underwent BAV with simultaneous aortography which revealed left main stem occlusion. The procedure was stopped and the patient went forward for repeat surgery. Patient 2 underwent successful ViV‐TAVI with a 26‐mm CoreValve with a guide catheter in the left main, but on removal coronary obstruction occurred, necessitating valve snaring into the aorta. Among the successful cases, (patients 3, 4, 5, 6) the TAVIs used were CoreValve Evolut R 23 mm ( n  = 3), and Lotus 23 mm ( n  = 1). In the successful cases the peak gradient fell from 83.0 to 38.3 mm Hg. No patient was left with >1+ AR. One patient had a stroke on Day 2, with full neurological recovery. Two patients underwent semi‐elective pacing for LBBB and PR >280 ms. Conclusions: ViV‐TAVI in stentless Freedom Solo valves is high risk. The risk of coronary occlusion is high. The smallest possible prosthesis (1:1 sizing) should be used, and strategies to protect the coronary vessels must be considered. © 2016 Wiley Periodicals, Inc.